The use of lexical cohesion elements in the writing of ESL learners - Kadiri, Goodluck C.; Igbokwe, Uche Lebechi; Okebalama, Udodirim Ngozi; Egbe, Cajetan Ikechukwu (Research in Language, 2016)
This study investigated the use of lexical elements of cohesion in the essay writing of students of English as a Second Language. Two hundred essays of final year students of the University of Nigeria, Nsukka were collated and analyzed by the researchers in order to identify the lexical elements used to achieve cohesion in writing. The result showed that students used three lexical elements as postulated by Gutwinski in varying degrees in their writings. These include: repetition, synonyms, and lexical sets (collocations). Students tended to use more of repetitions and made minimal use of synonyms and lexical sets to achieve cohesion in writing. This has led to poorly written essays by students. It also implies that lexical cohesion elements should be taught in schools to enable students use them appropriately in writing.